2019
DOI: 10.3390/nu11123058
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Inhibitory Effects of Enteral Nutrition Formula on Indomethacin-Induced Gastric Lesions in Mice

Abstract: We investigated the effects of enteral nutrition formula on non-steroidal anti-inflammatory drug (NSAID)-induced gastric lesions in mice. Male ICR mice aged 7–9 weeks old were fasted, then orally given either purified water, Mermed® One, or 2-fold diluted Terumeal® 2.0α as enteral nutrition (25 or 50 mL/kg each). Indomethacin (IND) was orally administered at 20 mg/kg after 30 min, and the stomach was removed 6 h later and fixed in formalin. The number and area of lesions in the stomachs of the mice given enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…On the other hand, such lesions were present in the groups that had received subcutaneous IND injections ( Figure 2 ), indicating that these injections had successfully produced a mouse model of gastric lesions. The results of these observations were similar to those seen when the same IND dose was administered orally [ 15 ]. Measurements of the number and area of gastric lesions showed that they were both lower in the EN_M + IND and EN_T + IND groups than in the water + IND group (percentage of numbers: EN_M + IND 89%, EN_T + IND 56%; area: EN_M + IND 61%, EN_T + IND 34% compared to the water + IND group) ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…On the other hand, such lesions were present in the groups that had received subcutaneous IND injections ( Figure 2 ), indicating that these injections had successfully produced a mouse model of gastric lesions. The results of these observations were similar to those seen when the same IND dose was administered orally [ 15 ]. Measurements of the number and area of gastric lesions showed that they were both lower in the EN_M + IND and EN_T + IND groups than in the water + IND group (percentage of numbers: EN_M + IND 89%, EN_T + IND 56%; area: EN_M + IND 61%, EN_T + IND 34% compared to the water + IND group) ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 83%
“…We have previously shown that the oral administration of two types of enteral nutrition formula (EN_M and EN_T) was effective in suppressing gastric lesions induced by oral IND administration in mice [ 15 ]. It was suggested that the mechanism whereby orally administered enteral nutrition formulas prevented gastric lesions might involve some sort of interaction between the formula and IND while both were simultaneously present in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations